The Influence of Individual Career and Career Development Programs on Organizational Commitment of Lecturers Politeknik Kutaraja Banda Aceh City with Job Satisfaction as A Variable Mediating - Akbar, Indra; Ariansyah, Ricky; Aini, Zahriatul (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
This study aims to determine the effect of individual careers and career development programs to organizational commitment and job satisfaction as a mediating variable. The sample used in this study is a lecturer at the Politeknik Kutaraja Banda Aceh, amounting to 114 people. Methods this study used a questionnaire as a research instrument. Simple random sampling is used as a sampling technique. This technique is used at random because it provides equal opportunity to all members of the population to be designated as members of the sample. The data were then analyzed using path analysis techniques (path analysis). The results of this study indicate that individual career effect on job satisfaction, career development programs affect job satisfaction, individual career affect organizational commitment, charisma development programs affect organizational commitment, job satisfaction affects organizational commitment, individual career not effect on organizational commitment through job satisfaction, and career.